2021
DOI: 10.1186/s13063-020-04959-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different acupuncture treatment methods on post-stroke cognitive impairment: study protocol for a multicenter randomized controlled trial

Abstract: Background Cognitive impairment is a common dysfunction after stroke that seriously affects the overall recovery of patients. Cognitive rehabilitation training is currently the main treatment to improve cognitive function, but its curative effect is limited. Acupuncture is a core component of traditional Chinese medicine (TCM), and some previous clinical studies have shown that it might be effective in treating post-stroke cognitive impairment (PSCI), but further evidence from large-sample stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Modern research has also shown that electroacupuncture is safe and effective in improving cognitive function, and can further enhance efficacy in a short period of time, potentially serving as a complementary treatment for PSCI [ 27 ]. In addition, some studies have suggested that electroacupuncture may improve PSCI at multiple levels and targets in various brain regions by improving damage to the central cholinergic system, enhancing synaptic plasticity, promoting the expression of neurotrophic factors, inhibiting inflammatory factors, regulating cellular autophagy, reducing oxidative stress, and establishing collateral circulation [ 28 ]. The specific mechanisms of action, however, remain unclear and further investigation is needed to elucidate these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Modern research has also shown that electroacupuncture is safe and effective in improving cognitive function, and can further enhance efficacy in a short period of time, potentially serving as a complementary treatment for PSCI [ 27 ]. In addition, some studies have suggested that electroacupuncture may improve PSCI at multiple levels and targets in various brain regions by improving damage to the central cholinergic system, enhancing synaptic plasticity, promoting the expression of neurotrophic factors, inhibiting inflammatory factors, regulating cellular autophagy, reducing oxidative stress, and establishing collateral circulation [ 28 ]. The specific mechanisms of action, however, remain unclear and further investigation is needed to elucidate these effects.…”
Section: Discussionmentioning
confidence: 99%
“…The head acupoints, including GV20, as widely used to treat mental disorders in Traditional Chinese Medicine (TCM). 10 In the previous studies of acupuncture fMRI, the number of acupoints were not completely consistent. The changes of brain activity induced by acupoints combination could be overlapped or antagonized.…”
Section: Introductionmentioning
confidence: 86%
“…As a result of these advantages, acupuncture has received continued interest from the general public and health professionals ( 19 ). Furthermore, a growing number of healthcare institutions have used acupuncture clinically and have shown that acupuncture can be a prospective therapeutic measure to enhance cognitive function in patients with PSCI ( 20 , 21 ). Meanwhile, animal models of PSCI have been used to explore the potential mechanisms of acupuncture treatment to achieve maximum benefit ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%